2016
DOI: 10.1080/15614263.2016.1268959
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring the validity of police use of force training

Abstract: This research examined the skills and abilities required of officers to effectively manage situations where the use of force may be required. The research also considered the nature of training required to facilitate the development of these skills/abilities. Seventy Western Australia Police officers participated in focus groups. Identified skills/abilities fell into seven categories: Aware, Assess, Approach, Act, Automatic, Appraise and Adapt. With regard to developing proficiency in these skills, officers em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 20 publications
2
68
0
Order By: Relevance
“…rather than the whole programme of police development. Concerning training programmes for coping with physical conflict situations, empirical studies have begun to paint a picture of the range of skills needed to deal with such situations (Preddy et al 2019b;Rajakaruna et al 2017) and to different formats of delivery (Renden et al 2016). Yet, besides analysis of police self-defence and arrest training (Cushion 2020), there is no known holistic account of the delivery of police training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…rather than the whole programme of police development. Concerning training programmes for coping with physical conflict situations, empirical studies have begun to paint a picture of the range of skills needed to deal with such situations (Preddy et al 2019b;Rajakaruna et al 2017) and to different formats of delivery (Renden et al 2016). Yet, besides analysis of police self-defence and arrest training (Cushion 2020), there is no known holistic account of the delivery of police training.…”
Section: Introductionmentioning
confidence: 99%
“…Proposals to tackle this observed lack of transfer, regularly include improving organizational structures to provide more training time (Buttle 2007;Jager et al 2013;Renden et al 2015a); revising what is taught (Renden et al 2015a;Renden et al 2016) and how it is taught (Cushion 2020; Nota and Huhta 2019;Staller and Zaiser 2015). Research so far has mostly investigated the structure and delivery of police training by interviewing trainee officers (Buttle 2007;Rajakaruna et al 2017) and trainers (Körner et al 2019;Preddy et al 2019b Abraham et al 2015) did Cushion (2020) provide empirical evidence about the actual delivery of police training. Using a case study approach and employing participant observation, interviews and time-on-task analysis, Cushion participated and observed three, two-day courses of officers' safety training in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent and repetitive training through use of force scenarios is needed that is inclusive of a wide variety of variables to best prepare officers for such circumstances. Rajakaruna, Henry, Cutler, and Fairman (2017) found that the focus of training should shift from performance and assessment to one that continually develops skills by practicing and learning. Situations that differ from the typical scenario take longer to process (Belmore & Hubbard, 1987), and officers who are slower in reacting may be at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Competencies of interest can be very specific, such as emotional resilience and information processing, for example if the assessment takes place after an absence due to psychological complaints ( Ingram et al, 1998 ). In contrast, if police organizations carry out the test as a pre-employment selection tool, they may choose a wide range of psychological competencies of interest consisting of emotional, social, and cognitive factors, such as motivational and communications skills (e.g., Adang, 2011 ; Rajakaruna et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%